Robinson Crusoe - Defoe, Daniel, 1661?-1731; Kincaid, Jamaica (Restless classics., 2019)
"Three centuries after Daniel Defoe published Robinson Crusoe, this gripping tale of a castaway who spends thirty years on a remote tropical island near Trinidad, encountering cannibals, captives, and mutineers before being ultimately rescued, remains a classic of the adventure genre and is widely considered the first great English novel. But the book also has much to teach us, in retrospect, about entrenched attitudes of colonizers toward the colonized that still resound today."--Page 4 of cover.